Mass flow rate measurement in a transonic turbine test facility with temperature distortion and swirl - Beard, P; Povey, T; Ireland, P (2008)
This paper describes the development and implementation of a system to perform accurate measurements of mass flow rate in the Isentropic Light Piston (Turbine) Facility (ILPF) at QinetiQ Farnborough. The facility has recently been upgraded so that turbine aerodynamic efficiency measurements can be performed. The implementation of a system for mass flow rate measurement formed part of that upgrade. The measurement system is novel in that accurate measurements can be performed with both combustor representative turbine inlet temperature distortion (hot-streaks) and swirl. The ILPF is a short-duration (approximately 0.5 s run time) turbine test facility, which has been used for aerodynamic and heat transfer investigations of-primarily-high-pressure turbine stages, although it has also been configured to operate as a 1 frac(1, 2) stage (HP stage with IP or LP vane) turbine. The MT1 turbine is a highly-loaded unshrouded design relevant to modern military engine design, or future civil engine design. The turbine is engine scale, and all relevant dimensional parameters for aerodynamics and heat transfer are matched: Re, M, N / sqrt(T01), Tgas / Twall. Hot streaks are simulated in the ILPF by the controlled mixing of hot and cold gas streams. The cold stream is introduced though a conventional sonic metering nozzle, from a large reservoir acting in blow-down mode. The hot stream is generated using a light free piston contained within a piston-tube, which, under the action of a driver gas, isentropically compresses and heats the working gas to the desired hot-gas temperature. The exit contraction of the piston tube acts as a subsonic converging-diverging venturi: upstream p0 and T0, and throat p are measured at a number of circumferential locations around the exit contraction to determine the mass flow rate of the hot stream. The effective area of the venturi was measured using a novel blow-down calibration technique which is described. The bias error in the measurement of mass flow rate through the turbine with and without temperature distortion was 1.13% and 1.37% respectively-of the same order as the accuracy associated with conventional tertiary devices. The precision uncertainty was 0.198% in both cases. Accuracy with the introduction of inlet swirl is 1.37%. © 2008 Elsevier Ltd. All rights reserved.